The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1982
DOI: 10.1002/art.1780250512
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen and glucocorticoid receptors in adult canine articular cartilage

Abstract: The cytoplasmic and crude nuclear fractions of adult mongrel dog articular cartilage contained estradi-01-and dexamethasone-binding components which had properties of physiologic steroid receptors. The equilibrium dissociation constants averaged 0.37 nM for estradiol and 2.27 nM for dexamethasone. The concentrations of estrogen receptors ranged from below 6 to 101 fmolhg protein in the cytosols and from below 2.8 to 17.5 fmol/pg DNA in the nuclear fractions. Glucocorticoid receptors were detected in only 4 of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
1
2

Year Published

1984
1984
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(17 citation statements)
references
References 17 publications
2
12
1
2
Order By: Relevance
“…Unlike the articular cartilage which contains oestrogen (Rosner, Manni, Malemud et al 1982;Young & Stack, 1982) as well as glucocorticoid (Young & Stack, 1982) binding sites, the present study detected only the specific binding of dexamethasone but not oestrogen in epiphysial chondrocytes, indicating an indirect action of oestrogen on this tissue. The high affinity dexamethasone binding component has a dissociation constant and a displacement by steroids in a manner similar to that shown for cytosol binding sites in embryonic chick cartilage (Kd 7-4 nmol/1) (Lee, Hicks, Hughes et al 1978) and dog articular cartilage (Kd 1-3 nmol/1) (Young & Stack, 1982).…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…Unlike the articular cartilage which contains oestrogen (Rosner, Manni, Malemud et al 1982;Young & Stack, 1982) as well as glucocorticoid (Young & Stack, 1982) binding sites, the present study detected only the specific binding of dexamethasone but not oestrogen in epiphysial chondrocytes, indicating an indirect action of oestrogen on this tissue. The high affinity dexamethasone binding component has a dissociation constant and a displacement by steroids in a manner similar to that shown for cytosol binding sites in embryonic chick cartilage (Kd 7-4 nmol/1) (Lee, Hicks, Hughes et al 1978) and dog articular cartilage (Kd 1-3 nmol/1) (Young & Stack, 1982).…”
Section: Discussioncontrasting
confidence: 79%
“…The high affinity dexamethasone binding component has a dissociation constant and a displacement by steroids in a manner similar to that shown for cytosol binding sites in embryonic chick cartilage (Kd 7-4 nmol/1) (Lee, Hicks, Hughes et al 1978) and dog articular cartilage (Kd 1-3 nmol/1) (Young & Stack, 1982). The level of receptor (1740 sites/cell) is low compared to rabbit articular chondrocytes monolayer (40000 sites/cell) (Blondelon, Adolphe, Zizine & Lechat, 1980).…”
Section: Discussionmentioning
confidence: 85%
“…To our knowledge only oestradiol receptors have been described in articular chondrocytes. '3 14 These receptors were found in small amounts but showed high affinity, which may justify saturation at physiological concentrations. It should also be noted that the lower concentrations used in our in vitro studies correspond approximately to physiological concentrations of free sex steroids, given that these hormones are bound to carrier proteins in excess of 90%.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that growth induced by sex hormones was not always associated with increases in serum GH or IGF-1.6.7 In addition, receptors for 17P-estradiol have been found in the epiphyses of mouse tibiae,sI cultured normal human osteoblast-like ~ells,l6~5* osteoblast-like osteosarcoma cells,23 and avian osteoclasts,53 as well as in fracture healing.54 Moreover, estradiol receptors have been found in articular cartilage. [55][56][57][58][59] Testosterone, which is the most abundant androgen, is metabolized in target tissues to dihydrotestosterone (DHT) or androstenedione by 5-alpha reductase before binding to its receptor. -3 This also appears to occur in chondrocytes from epiphyseal and articular cartilage.64.65 Recently, receptors for DHT were also found in osteoblasts24.66 and epiphyseal chondrocytes.38 However, some tissues do not have the appropriate enzymes to convert testosterone to DHT and testosterone functions dire~tly.57.…”
Section: Introductionmentioning
confidence: 99%